Root-Cause Investigation and Technical Reliability Analysis of the Starting-Air System Failure in a Marine Generator A Case Study of KM Sabuk Nusantara 101 - Gaspar Pereira Maia Pinto (G-Tech: Jurnal Teknologi Terapan, 2026)
The starting-air system of the 114-kW main generator aboard KM Sabuk Nusantara 101 experienced repeated start failures during a 14-day sea operation, resulting in delayed engine activation and reliability reduction. This study aims to identify the root causes of the failure and evaluate the system’s technical reliability performance. The investigation employed field observation, pressure measurement, functional testing, fault tracing, and logbook analysis, supported by Root-Cause Analysis (RCA) and reliability metrics (MTBF, MTTR, and failure rate). The results show three dominant failure sources: (1) air receiver leakage due to degraded flange seals, (2) solenoid valve contamination causing pilot pressure loss, and (3) starting-air valve seat wear leading to insufficient cylinder impulse pressure. Reliability calculation produced an MTBF of 112 hours, MTTR of 2.5 hours, and a failure rate of 0.00893 h⁻¹, indicating low operational reliability despite 97.8% availability. The findings conclude that the system failure is dominated by leakage, contamination, and single-point failures (SPF) in the pneumatic control circuit. Preventive actions recommended include condition-based monitoring, improved sealing and filtration, functional inspection intervals every 250 hours, and redundancy for critical pneumatic components. These measures are expected to increase operational readiness and reduce downtime on similar shipboard installations.